Empowering confident communication skills and SEL in the ELT classes - Nino Putkaradze (Foundations and Trends in Modern Learning, 2024)
Empowering confident communication skills in English Language Teaching (ELT) classes is crucial for learners to effectively express themselves and engage in meaningful interactions. This abstract explores various strategies and approaches that teachers can employ to enhance students’ confidence in using English as a second language. By creating a supportive and inclusive classroom environment, providing opportunities for authentic communication, integrating speaking and listening activities, offering constructive feedback, and promoting self-expression, teachers can help students develop the confidence needed to communicate confidently in English. This abstract highlights the importance of empowering students with the necessary skills and mindset to navigate real-world communication situations and succeed in their language learning journey.